Intention in Using Nursing Information Systems with Unified Theory of Acceptance Theory Approach and Use of Technology in Kendari Government Hospital - Zahalim; Ahsan; Viera Wardhani (International Journal of Science and Society, 2022)
A nursing information system is a combination of computer science, information science, and nursing science designed to assist the management and processing of nursing data, information, and knowledge to support nursing practice and care delivery. Unified Theory Acceptance and Use of Technology (UTAUT) is a model theory used to identify Behavioural Intention in using nursing care information systems. The purpose of this study was to analyse the behavioural intention of nurses on the use of nursing care information systems in the inpatient ward of the Kendari government hospital with the UTAUT approach. The data was obtained using a questionnaire which was distributed directly to nurses, totalling 143 people. Data analysis used rank Spearman with SPSS 16. Relationship between performance expectancy and behavioural intention in nurses = 0.000 (<0.05), and R = 0.435, Relationship between effort expectancy and behavioural intention =0.000 (<0.05), and R= 0.605. The relationship between social influence and behavioural intention = 0.000 (<0.05), and R = 0.671. The results of the study show that performance expectancy, effort expectancy and social influence have a positive and significant effect on behavioural intention in using information systems. Most nurses have a good intention in the use of nursing care information systems (SIAK) in inpatient rooms. Performance EXPECTANCY, effort and social influence have a positive and significant relationship. The most influential variable on the behavioural intention in using SIAK is the social influence variable.